BRIT1/MCPH1 is essential for mitotic and meiotic recombination DNA repair and maintaining genomic stability in mice. - Yulong Liang; Hong Gao; Shiaw-Yih Lin; Guang Peng; Xingxu Huang; Pumin Zhang; John A Goss; Francis C Brunicardi; Asha S Multani; Sandy Chang; Kaiyi Li (PLoS Genetics)
BRIT1 protein (also known as MCPH1) contains 3 BRCT domains which are conserved in BRCA1, BRCA2, and other important molecules involved in DNA damage signaling, DNA repair, and tumor suppression. BRIT1 mutations or aberrant expression are found in primary microcephaly patients as well as in cancer patients. Recent in vitro studies suggest that BRIT1/MCPH1 functions as a novel key regulator in the DNA damage response pathways. To investigate its physiological role and dissect the underlying mechanisms, we generated BRIT1(-/-) mice and identified its essential roles in mitotic and meiotic recombination DNA repair and in maintaining genomic stability. Both BRIT1(-/-) mice and mouse embryonic fibroblasts (MEFs) were hypersensitive to gamma-irradiation. BRIT1(-/-) MEFs and T lymphocytes exhibited severe chromatid breaks and reduced RAD51 foci formation after irradiation. Notably, BRIT1(-/-) mice were infertile and meiotic homologous recombination was impaired. BRIT1-deficient spermatocytes exhibited a failure of chromosomal synapsis, and meiosis was arrested at late zygotene of prophase I accompanied by apoptosis. In mutant spermatocytes, DNA double-strand breaks (DSBs) were formed, but localization of RAD51 or BRCA2 to meiotic chromosomes was severely impaired. In addition, we found that BRIT1 could bind to RAD51/BRCA2 complexes and that, in the absence of BRIT1, recruitment of RAD51 and BRCA2 to chromatin was reduced while their protein levels were not altered, indicating that BRIT1 is involved in mediating recruitment of RAD51/BRCA2 to the damage site. Collectively, our BRIT1-null mouse model demonstrates that BRIT1 is essential for maintaining genomic stability in vivo to protect the hosts from both programmed and irradiation-induced DNA damages, and its depletion causes a failure in both mitotic and meiotic recombination DNA repair via impairing RAD51/BRCA2's function and as a result leads to infertility and genomic instability in mice.